2014
DOI: 10.1080/10942912.2012.714828
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Therapeutic Effects of Soybean (Glycine Max)

Abstract: Soybeans contain nutritional and medicinal properties. It is a rich source of quality proteins, phytosterols, fibers, and other biologically active compounds, notably daidzein and genistein. Soybeans provide health benefits due to their functional ingredients such as proteins, polysaccharides, and isoflavones. These functional ingredients play a vital role in the reduction of different types of cancer, cardiovascular diseases, postmenopausal problems, diabetes, and some neurodegenerative disorders. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 174 publications
(171 reference statements)
0
27
0
1
Order By: Relevance
“…It is influenced by physicochemical parameter of dough (Ahmad et al, 2014). It is influenced by physicochemical parameter of dough (Ahmad et al, 2014).…”
Section: Sensory Characteristics Of Gf Bread With Different Levels mentioning
confidence: 99%
See 2 more Smart Citations
“…It is influenced by physicochemical parameter of dough (Ahmad et al, 2014). It is influenced by physicochemical parameter of dough (Ahmad et al, 2014).…”
Section: Sensory Characteristics Of Gf Bread With Different Levels mentioning
confidence: 99%
“…Enriched or fortified GF products improve the quality of GF diet (Jideani & Onwubali, 2009). Soybean could be an essential part of functional foods, as well as it could be used for enhancement of product quality (Ahmad et al, 2014). Soybean also contains up to 45% protein (Islam, Chowdhury, Islam, & Islam, 2007) with a digestibility value of 91.41% (Zhao et al, 2014) and as a good source of vitamins and mineral supplies adequate amount of different amino acids required for repairing the damaged body tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soy protein can improve glucose tolerance [Ahmad et al, 2014]. OGTT results showed that okara delayed the increase of postprandial glucose level and signifi cantly reduced postprandial glucose peak versus DCG.…”
Section: Discussionmentioning
confidence: 98%
“…Soy products are gaining popularity for soybean is nutritionally rich, and contain health promoting ingredients, such as phytosterols, fibers, daidzein, genistein, and other bioactive peptides (Ahmad et al, 2014). Lactic acid bacteria (LAB) and Ba.…”
Section: Introductionmentioning
confidence: 99%